BIOM-22. BMX EXPRESSION LEVEL IN GLIOBLASTOMA PREDICTS HYPERSENSITIVITY TO IBRUTINIB TREATMENT. (14th November 2022) - Shakya, Sajina; Sundar, Swetha; Recinos, Violette; Hubert, Christopher
Abstract: Glioblastoma (GBM) is the most prevalent and aggressive form of primary brain cancer and is notoriously drug and radiation resistant. The tumor recurrence and therapeutic resistance typically seen in GBM are largely driven by a small population of self-renewing, highly tumorigenic cells termed cancer stem cells (CSCs). The stem-cell-like properties of GBM CSCs are promoted, at least in part, by abnormal activation of the Janus kinase/signal transducer and activator of transcription 3 (JAK/STAT3) signaling pathway. This activation can occur through aberrant expression of bone marrow and X-linked (BMX) protein, a non-receptor tyrosine kinase that is upregulated in glioma stem cells and may be targeted by the drug ibrutinib, currently undergoing clinical trials in GBM. In contrast, BMX is not expressed in normal non-cancerous stem cells of the brain. We discovered a striking dissimilarity where a subset of our patient-derived GBM specimens are up to 100-fold more sensitive to ibrutinib than others. We investigated the mechanisms behind this hypersensitivity by analyzing the expression levels of JAK/STAT3 signaling proteins. Here we discovered that the baseline expression value of BMX prior to treatment has a strikingly high predictive value for later later response to ibrutinib, primarily explaining the variation in a specimen's ibrutinib sensitivity. Furthermore, we found that pediatric GBM tumor models are typically BMX-low and most likely to be hypersensitive to ibrutinib compared to their adult counterparts. Ibrutinib further suppresses GBM and DIPG proliferation in CSC-rich proliferative regions of organoid models. Our data suggest the potential use of BMX as a predictive biomarker of ibrutinib sensitivity, and provide an impetus for mechanistic and preclinical investigation of ibrutinib sensitivity, particularly in pediatric disease.